(3ebGeGJ GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3ef GdebGeI GdhQOjI bhdg(B: (3MOKfG GdQjGf Yf CHj GdQjMGf Yf CHj GdhQO CHGf, Yf HdHd GdCZUGf s
(3BNQgG (B:s
(3ef GdebGeI GdjGbhJjI acCfg bVH GdRHQLO CNVQ bO beYhG CWQGag ajQhRLG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI QGHYIs
(3HgG fXGe GdJYbjHIs
(3YOOgG ebGeGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs